POSTURAL CHANGES IN BLOOD PRESSURE ASSOCIATED WITH AGEING: Life Sciences-Physiology - KARTHEEK, BALAPALA R.; KUMAR, GANESAN; AMEERUNNISA BEGUM, S.; VENKATESWARAIAH, SIVAYOGI (International Journal of Life Science and Pharma Research, 2011)
The present study reveals to determine the patterns of orthostatic blood pressure (OBP) changes, symptoms and clinical factors in different aged groups. Sixty subjects of different aged group between 20 and 90 were used in this study. Among these groups, different measurements of BP were done in lying as well as standing position at two time intervals (1min, 3min) to check their orthostatic hypotension (OH). The Results showed that OH significantly increased in the age group 71.1 and moderate in 39.8 and no changes occurred in 20.55. The symptoms of head ache, blurred vision, falling and light headedness as well as blood hemoglobin levels were independent of OH in all aged groups. Based on the nutritional status, Body Mass Index was measured in these subjects and identified as 72% well nourished; 4% under-nourished and 24% overweight. The systolic OH (P<0.01) was more common among the elderly subject than diastolic OH (P>0.05). Also prevalence was similar in either gender of elderly group. Based on the present study, we conclude that OH incidence increases with increase in age and symptoms are independent of physical recording.